On the Characteristic Operators and Projections and on the Solutions of Weyl Type of Dissipative and Accumulative Operator Systems. III. Separated Boundary Conditions - Khrabustovsky, V. I. (Журнал математичної фізики, аналізу, геометрії, 2006)
For the systems as in the title, boundary-value problems with separated boundary conditions are considered. We prove that the characteristic operator of such problem admits a special expression in terms of the projection (characteristic projection). This allows one to introduce for the above systems the analogues of the Weyl functions and solutions, to establish for them the Weyl type inequalities which turn out to be well known in a number of special cases. Mathematics Subject Classification: 34B07, 34B20, 34G10, 47A06.